Evaluation of Soybean Resistance to Pod-Sucking Bug, Riptortus linearis F. and Performance of its Agronomic Characters - Ayda Krisnawati; Mochammad Muchlish Adie (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Pod sucking bug, Riptortus linearis, is the most damaging soybean pest in Indonesia. A total of 24 soybean genotypes was identified for their resistance to pod sucking bug. The objective of the study was to classifying the resistance of some soybean genotypes against pod sucking pests. The research was conducted during the second dry season (July - October) 2016 in Ngale Research Station, East Java, Indonesia. The experimental design was arranged in randomized block design with five times repetition and two types of environment (full crop protection and controlled until 50 days of planting/dap). The resistance to pod sucking bug was evaluated based on seed damage, pod damage, and seed weight. The grouping of resistance was by using Chiang Talekar’s method (1980). A very high natural population of pod sucking bug was recorded in the research area as seen from the average number of damaged pod in full protection environment (L1) and insecticide control until 50 dap (L2), i.e. 41.45% and 60.16%, respectively. Genotype of G511H/Anj//Anj-2-8 was consistently resistant to pod sucking bug in L1 as well as L2. This genotype also had early days to maturity (78 days) and large seed size (15.57 g/100 seed), thus potentially to be developed in tropical area of Indonesia. The availability of genotype with such characteristics is in accordance with farmers’ preference and also important to minimize yield losses.